2004
DOI: 10.1146/annurev.fluid.36.050802.122103
|View full text |Cite
|
Sign up to set email alerts
|

TURBULENT FLOWS OVER ROUGH WALLS

Abstract: ▪ Abstract We review the experimental evidence on turbulent flows over rough walls. Two parameters are important: the roughness Reynolds number [Formula: see text], which measures the effect of the roughness on the buffer layer, and the ratio of the boundary layer thickness to the roughness height, which determines whether a logarithmic layer survives. The behavior of transitionally rough surfaces with low [Formula: see text] depends a lot on their geometry. Riblets and other drag-reducing cases belong to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

78
916
6
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,255 publications
(1,001 citation statements)
references
References 73 publications
78
916
6
1
Order By: Relevance
“…Figure 2(b) shows the well-established empirical relationship between drag and λ F . This has been observed in previous studies on rough-wall boundary layers as reported by Grimmond & Oke (1999) and Jimenez (2004). However, the effect of plan solidity on bulk quantities is not clear.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Figure 2(b) shows the well-established empirical relationship between drag and λ F . This has been observed in previous studies on rough-wall boundary layers as reported by Grimmond & Oke (1999) and Jimenez (2004). However, the effect of plan solidity on bulk quantities is not clear.…”
Section: Introductionsupporting
confidence: 68%
“…These variations follow the dotted and dot-dashed lines in figure 2(a). The different cases were designed on the basis of previous studies that show the location of the peaks in y 0 at λ P = 0.27 and λ F = 0.15 (Grimmond &Oke 1999 andJimenez 2004). Progressive repositioning of the downstream roughness elements in the sheltered regions of the upstream obstacles, has allowed us to achieve variations in plan solidity at fixed frontal solidity.…”
Section: Roughness Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Dependent on whether k is based on S a , S q or S z,5×5 , the ratio δ/k varies between ≈37 and 6. Jiménez (2004) states that universal behaviour in the outer layer should be observed for cases where δ/k > 40. We will see later that S z,5×5 is close to the equivalent sand-grain roughness of the surfaces and thus appears to be a suitable measure for k. The resulting δ/k = 6 indicates that we are in a regime where a certain degree of non-universal behaviour can be expected, but this regime is of high practical relevance, since in many examples of turbulent flow over rough surfaces δ/k is significantly lower than 40 (Sadeh, Cermak & Kawatani 1971;Bogard, Schmidt & Tabbita 1998;Wood et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…García-Mayoral & Jiménez [8] identified drag-reduction regimes, gathering in one previously proposed theories [14,4,9,10]. For low Reynolds number or small riblets, effects are well-characterized by ∆ h. When size or Reynolds increases, break-down mechanisms, based on Kelvin-Helmotz instabilities, cancel out the beneficial viscous effect.…”
Section: Introductionmentioning
confidence: 96%